Conduct against the thyroid nodule - Delgado, Bolívar; Yametti, Luis; Crocci, Fabio; Lanza, Mario; Gastambide, Carmelo (Cirugía del Uruguay, 1982)
The authors analyze the charateristics of the thyroid nodules regarding the possibility of cancer, emphasizing the high risk factors in that respect. They maintain that the thyroid nodules should not be operated on systematically fearing cancer; it is necessary instead to select only those patients that present several high risk factors for that treatment.